Unmet Primary Care Needs in Diabetic Patients with Multimorbidity in a Medically Underserved Area. (5th May 2017) - Jackson, Bianca M.; Gutierrez, Mary Lou; Relyea, George E.; Carlton, Erik L.; Ahn, SangNam; Binkley, Bonnie L.; Bailey, James E.
Background: Diabetic patients with multimorbidity in medically underserved minority communities are less engaged in primary care and experience high emergency department (ED) utilization. This study assesses unmet primary care needs among diabetic patients in a medically underserved area (MUA). Community Context: A suburb of Memphis—Whitehaven, Tennessee (Shelby County, ZIP codes 38109 and 38116)—majority African American (96.6%) with 30.5% below the poverty level. Methods: Community case study using multiple data sources including diabetes registry, individual interviews, focus groups, and a survey of 30 ED patients with diabetes and multimorbidity. Results: Diabetes registry data indicated that 95.5% of 5723 diabetic patients had multimorbidity. Over 91.5% were uncontrolled at some point in 2014 to 2015. Only 83% of patients with diabetes and multimorbidity reported having a primary care provider (PCP) and those without a PCP were more likely to report delays in needed care. Patients expressed strong interest in health coaching (88%) and receiving text messages from the doctor's office (73%). Individual patient interviews (n = 9) and focus groups (n = 11) revealed common primary care and self-care experiences and needs including diabetes education, improved patient–provider communication, health-care access and coverage, and strengthened primary care and community. Conclusion: This study demonstrates that almost 1 in 5 ED complex diabetic patients in an MUA do not have a PCP, and that difficulty accessing primary care often results in patients forgoing needed care. Qualitative findings support these conclusions. These results suggest that primary care capacity and infrastructure to support diabetes self-care need strengthening in MUAs.